TRADISI MAKATTE PADA PEREMPUAN BUGIS: MAKNA RELIGIUS DAN DAMPAKNYA TERHADAP KESEHATAN REPRODUKSI - Muhammad Ridha Afdhal; Dicky Indirwan (Illea : Journal of Health Sciences, Public Health and Medicine, 2026)
Makkatte (female circumcision) among the Bugis ethnic group is a tradition deeply embedded with religious significance; however, it has generated ongoing debate due to its potential clinical risks to female genital health. This study aims to examine the persistence of the makatte tradition, explore its underlying meanings, and analyze its actual implications for women's reproductive health. The study involved 12 key informants, including midwives, sanro (traditional healers), customary leaders, parents, and women who had undergone circumcision. A qualitative case study approach was employed, utilizing field observations, in-depth interviews, and secondary document analysis as data collection methods. The findings reveal that makatte is profoundly understood within the community as a symbol of purity, moral cleansing, and the affirmation of a young girl's religious identity. Nevertheless, from a biomedical perspective, the practice of physically injuring genital tissue lacks any clinical indication and carries substantial risks, including short-term complications such as bleeding and infection, as well as long-term consequences such as sexual dysfunction and keloid formation. The study concludes that the resilience of this tradition is largely sustained by collective decision-making processes within the extended family structure, thereby fostering strong cultural resistance to formal medical prohibitions.